В полете к солнцу: Стихи и поэмы: [Пер. с удм.] / Кузебай Герд - Герд Кузебай (Удмуртия, 1989)
Экземпляры: (20181023) / Инвентарный номер: 23213 / Цена: 1.10 / Сис.шифр: С / Авт.знак: Г37 / ББК: С(Удм)